2014
DOI: 10.1007/s10147-014-0741-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of therapeutic results from radiofrequency ablation and stereotactic body radiotherapy in solitary lung tumors measuring 5 cm or smaller

Abstract: For lung tumor patients, lung RFA provided local tumor control and survival that were similar to those achieved using SBRT, with equal safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…This clinical evidence leads us to believe that RFA may become a new treatment modality following surgery, radiotherapy, and systemic therapy. However, the efficacy of RFA still needs to be validated in prospective, randomized, multi‐center clinical trials, and comparison with other treatment, including surgery, ablation and SBRT is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This clinical evidence leads us to believe that RFA may become a new treatment modality following surgery, radiotherapy, and systemic therapy. However, the efficacy of RFA still needs to be validated in prospective, randomized, multi‐center clinical trials, and comparison with other treatment, including surgery, ablation and SBRT is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…72 This clinical evidence leads us to believe that RFA may become a new treatment modality following surgery, radiotherapy, and systemic therapy. However, the efficacy of RFA still needs to be validated in prospective, randomized, multi-center clinical trials, 73 and comparison with other treatment, including surgery, [74][75][76][77] ablation 78 and SBRT [79][80][81][82] is necessary. In summary, the effectiveness and safety of RFA for the treatment of pulmonary tumors has been well demonstrated by clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Schlijper et al (1) reviewed 27 studies and identified that the treatment-related mortality rates for RFA and surgery were 0 and 1.4-2.4%, respectively, whereas morbidity rates were reported inconsistently but appeared to be the lower for surgery. The study by Ochiai et al (9) was conducted to compare the clinical outcomes of RFA with those of SBRT. The RFA and SBRT groups showed a similar 3-year local tumor progression (9.6 vs. 7.0%, p=0.746) and OS rates (86.4 vs. 79.6%, p=0.738).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis conducted on the National Cancer Institute's Surveillance, Epidemiology, and End Results database (n=1,897) found OS and cancer specific survival were not significantly different between propensity score matched NSCLC patients treated surgically or by ablation (19). In a comparative study between RFA and SBRT in patients (n=48 and 47, respectively) with NSCLC of <5 cm, 3-year local control and OS rates were similar (20).…”
Section: Editorialmentioning
confidence: 97%